Electric field effects on proteins – Novel perspectives on food and potential health implications. (November 2020) - Rodrigues, Rui M.; Avelar, Zita; Machado, Luís; Pereira, Ricardo N.; Vicente, António A.
Graphical abstract: Highlights: Recent developments of electric field processing on food proteins are discussed. Protein's biological function is mostly governed by its structure. Structure and conformation of proteins could be modified by electric fields. Electric field modulates functional, immunological and bioactive properties of food proteins. Electric fields bring novel functionalities on food proteins with a health impact. Abstract: Electric fields (EF) technologies have been establishing a solid position in emergent food processing and have seen as serious alternatives to traditional thermal processing. During the last decades, research has been devoted to elucidation of technological and safety issues but also fundamental aspects related with interaction of electric fields (EF) with important macromolecules, such as proteins. Proteins are building blocks for the development of functional networks that can encompass health benefits (i.e. nutritional and bioactive properties) but may be also linked with adverse effects such as neurodegenerative diseases (amyloid fibrils) and immunological responses. The biological function of a protein depends on its tridimensional structure/conformation, and latest research evidences that EF can promote disturbances on protein conformation, change their unfolding mechanisms, aggregation and interaction patterns. This review aims at bringing together these recent findings as well as providing novel perspectives about how EF can shape the behavior of proteins towards the development of innovative foods, aiming at consumers' health and wellbeing.